Management of Coronary Artery Diseases in Systemic Vasculitides: Complications and Strategies - Shumnalieva, Russka; Mileva, Niya; Padjen, Ivan; Siliogkas, Periklis; Chervenkov, Lyubomir; Bakopoulou, Konstantina; Kaouri, Issa El; Vasilska, Anna; Miteva, Dimitrina; Vassilev, Dobrin; Velikova, Tsvetelina (Medicina (Kaunas, Lithuania), 2024)
Coronary artery disease (CAD) presents a significant risk for patients with systemic vasculitides, a group of disorders characterized by the inflammation of blood vessels. In this review, we focus on the pathophysiological mechanisms, complications, and management strategies for CAD in systemic vasculitides. We highlight how the inflammatory processes inherent in vasculitis contribute to accelerated atherosclerosis and myocardial ischemia. Key strategies in managing CAD in this patient population include using medicine treatments to mitigate vascular inflammation while balancing the risk of promoting cardiovascular events and lifestyle modifications. Understanding the nuanced relationship between systemic vasculitides and CAD is crucial for improving patient outcomes and guiding therapeutic approaches.